1994
DOI: 10.1111/j.1528-1157.1994.tb02521.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Sensitivity and Photosensitivity in Epileptic Children with Visually Induced Seizures

Abstract: We evaluated photosensitivity and pattern sensitivity in 74 epileptic children (38 males, 36 females aged 4.4-19 years; mean age 11.9 years) with reflex seizures induced by environmental visual stimuli and analyzed clinical and EEG characteristics of patients according to type of sensitivity. Standard procedures of visual stimulation were used in all cases. Seven children were excluded because of poor cooperation (3) or no activation (4). Fifty-one percent of the remaining 67 patients showed sensitivity to bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 20 publications
4
30
0
2
Order By: Relevance
“…However, other authors have found a small proportion of pattern‐sensitive patients who were insensitive to intermittent photic stimulation. In a group of 67 children with visually induced seizures studied by Brinciotti et al (16), 51% exhibited sensitivity to both light and pattern, but 33% had isolated sensitivity to light and 16% to pattern. Among patients with television epilepsy and video‐game epilepsy, ∼20% are not responsive to intermittent light stimulation but are sensitive to patterns (6,32).…”
Section: Discussionmentioning
confidence: 98%
“…However, other authors have found a small proportion of pattern‐sensitive patients who were insensitive to intermittent photic stimulation. In a group of 67 children with visually induced seizures studied by Brinciotti et al (16), 51% exhibited sensitivity to both light and pattern, but 33% had isolated sensitivity to light and 16% to pattern. Among patients with television epilepsy and video‐game epilepsy, ∼20% are not responsive to intermittent light stimulation but are sensitive to patterns (6,32).…”
Section: Discussionmentioning
confidence: 98%
“…Photosensitive seizures of partial onset have been increasingly reported in recent literature (14)(15)(16). Most of the reported cases had photosensitive partial seizures of occipital origin (17), if not exclusively (1 8). Some investigators suggested that photosensitive partial seizures may have been underestimated and that this type of seizure constitutes around one third of seizures induced by TV or videogames (14,16).…”
Section: Czmentioning
confidence: 99%
“…Brinciotti et al39 also reported two families in which five members had pattern-sensitive epilepsy (three in one family and two in the other). In a group of children with visually induced seizures described by Brinciotti et al,40 two girls with both photosensitivity and pattern sensitivity were monozygotic twins.…”
Section: Discussionmentioning
confidence: 98%
“…Seven were female and five were male, with a female-to-male ratio of 1.4:1. Girls are reported to be nearly twice as likely to have pattern sensitivity as boys,9 however, Brinciotti et al10 noted a preponderance of males among patients with pattern sensitivity.…”
Section: Discussionmentioning
confidence: 99%